Determinan Ketimpangan Pendidikan di Indonesia Tahun 2022 - Sigalingging, Amelia Rahel; Silalahi, Agnes R.K.; Mahendra, Dafa Ryandika; Jonatan, Hotton; Purwoto, Agus (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Educational inequality is a longstanding issue in Indonesia. Uneven educational conditions are triggered by several specific factors. This study aims to identify the factors affecting educational attainment through the approach of the average length of schooling (RLS). The analytical method used is multiple linear regression. The analysis results show that the Percentage of Poor Population (PPM), the proportion of women aged 20-24 years who are married or living together before the age of 18, the student-teacher ratio, and the Open Unemployment Rate (TPT) significantly affect the average length of schooling in Indonesia. The increase in PPM and the proportion of married women tends to increase educational inequality in Indonesia, while the increase in the student-teacher ratio and TPT can reduce educational inequality in Indonesia.